Yellow fever control in Cameroon: Where are we now and where are we going? - Wiysonge, Charles Shey (BioMed Central, 2008)
BACKGROUND: Cameroon is one of 12 African countries that bear most of the global burden of yellow fever. In 2002 the country developed a five-year strategic plan for yellow fever control, which included strategies for prevention as well as rapid detection and response to outbreaks when they occur. We have used data collected by the national Expanded Programme on Immunisation to assess the progress made and challenges faced during the first four years of implementing the plan. METHODS: In January 2003, case-based surveillance of suspected yellow fever cases was instituted in the whole country. A year later, yellow fever immunisation at nine months of age (the same age as routine measles immunisation) was introduced. Supplementary immunisation activities (SIAs), both preventive and in response to outbreaks, also formed an integral part of the yellow fever control plan. Each level of the national health system makes a synthesis of its activities and sends this to the next higher level at defined regular intervals; monthly for routine data and daily for SIAs. RESULTS: From 2004 to 2006 the national routine yellow fever vaccination coverage rose from 58.7% to 72.2%. In addition, the country achieved parity between yellow fever and measles vaccination coverage in 2005 and has since maintained this performance level. The number of suspected yellow fever cases in the country increased from 156 in 2003 to 859 in 2006, and the proportion of districts that reported at least one suspected yellow fever case per year increased from 31.4% to 68.2%, respectively. Blood specimens were collected from all suspected cases (within 14 days of onset of symptoms) and tested at a central laboratory for yellow fever IgM antibodies; leading to confirmation of yellow fever outbreaks in the health districts of Bafia, Méri and Ntui in 2003, Ngaoundéré Rural in 2004, Yoko in 2005 and Messamena in 2006. Owing to constraints in rapidly mobilising the necessary resources, reactive SIAs were only conducted in Bafia and Méri several months after confirmation of the outbreak. In both districts, a total of 60,083 people (representing 88.2% of the 68,103 targeted) were vaccinated. Owing to the same constraints, SIAs were not conducted promptly in response to the outbreaks in Ntui, Ngaoundéré Rural, Yoko and Messamena. However, these four and two other health districts at high risk of yellow fever outbreaks (i.e. Maroua Urban and Ngaoundéré Urban) conducted preventive SIAs in November 2006, vaccinating a total of 752,195 people (92.8% of target population). In both the reactive and preventive SIAs, the mean wastage rates for vaccines and injection material were less than 5% and there was no report of a serious adverse event following immunisation. CONCLUSION: Amidst other competing health priorities, over the past four years Cameroon has successfully planned and implemented evidence-based strategies for preventing yellow fever outbreaks and for detecting and responding to the outbreaks when they occur. In order to sustain these initial successes, the country will have to attain and sustain high routine vaccination coverage in each successive birth cohort in every district. This would require fostering and sustaining high-level political commitment, improving the planning and monitoring of immunisation services at all levels, adequate community mobilisation, and efficient coordination of current and future immunisation partners.